2009
DOI: 10.1103/physrevlett.103.135001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organizing GeV, Nanocoulomb, Collimated Proton Beam from Laser Foil Interaction at7×1021W/cm2

Abstract: We report on a self-organizing, quasistable regime of laser proton acceleration, producing 1 GeV nanocoulomb proton bunches from laser foil interaction at an intensity of 7 x 10;{21} W/cm;{2}. The results are obtained from 2D particle-in-cell simulations, using a circular polarized laser pulse with Gaussian transverse profile, normally incident on a planar, 500 nm thick hydrogen foil. While foil plasma driven in the wings of the driving pulse is dispersed, a stable central clump with 1-2lambda diameter is form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 38 publications
3
53
0
Order By: Relevance
“…5(a), the foil thickness l 0 ¼ 0:5 is obtained based on Eqs. (2)- (5), (17), and (18), consistent with the theoretical results in Ref. [23].…”
Section: Effects Of Ion Motion On Cel Formationsupporting
confidence: 81%
See 1 more Smart Citation
“…5(a), the foil thickness l 0 ¼ 0:5 is obtained based on Eqs. (2)- (5), (17), and (18), consistent with the theoretical results in Ref. [23].…”
Section: Effects Of Ion Motion On Cel Formationsupporting
confidence: 81%
“…High-energy ions accelerated by such intense laser interacting with the solid target can be prospectively applied in fast ignition for inertial confinement fusion [3,4], medical therapy [5,6], and proton imaging [7], among others. Radiation pressure acceleration (RPA) using circularly polarized (CP) laser pulses provides a promising way to obtain a high-energy ion beam with monoenergetic spectrum in a much more efficient manner, compared with target normal sheath acceleration [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Yan et al [12] proposed the phase-stable-acceleration (PSA) mechanism in the RPA regime [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] to synchronously accelerate and bunch ions within skin depth of the laser pulse to get a monoenergetic ion beam in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Existing studies have shown that GeV proton beams can be obtained by RPA using circularly polarized (CP) lasers with intensity above 10 22 W/cm 2 . [14][15][16] However, because of transverse instabilities and hole-boring by the laser pulse, [14][15][16][17] the acceleration length is rather limited and it is difficult to enhance proton energy without still higher laser intensity. Recently, it has been shown that tens GeV proton beams 18,19 can be obtained by sequential radiation pressure and bubble acceleration or a moving double-layer, or in a two-phase acceleration regime 20,21 by ultra-relativistic lasers.…”
Section: Introductionmentioning
confidence: 99%
“…27,36,37 We investigate why and how the steepness a 0 / t up of the laser front plays a critical role in addition to the laser intensity, the plasma density, and the foil thickness. Here a 0 = eE L / m e L c is the normalized amplitude, m e and e are the electron mass and charge, respectively, E L is the laser electric field, L is the laser frequency, c is the light speed, and t up is the rising time of the laser pulse.…”
Section: Introductionmentioning
confidence: 99%